Neutron Permeation Properties and Characterization of Synthesized Non-Hydrated Magnesium Borate Minerals - Kipcak, Azmi Seyhun; Derun, Emek Moroydor; Senberber, Fatma Tugce; Ozdemir, Ozgul Dere; Baysoy, Derya Yilmaz; Piskin, Sabriye (ASIAN JOURNAL OF CHEMISTRY, 2014)
Magnesium borates are excellent materials due to their thermal and mechanical properties. In this study, the thermal (solid-state) synthesis was used for the production of ton-hydrated magnesium borate minerals. In the X-ray diffraction results of thermal Synthesis, Kotoite (K) 01-075-1807, Mg-3(BO3)(2); Suanite (S) 01=086-0531, Mg-2(B2O5) and (MgB1) 00-031-0787, VIg1,3407 and (MgB') 01-073-2232, Mg2B2O5 were produced. Higher XRD scores were seen at the molar ratios of 3:2 and 1:1. Materials, XRD scores increased With increasing temperature and time. Molar ratios, reaction temperature and time for the best crystal magnesium borate materials production were determined as 3:2-1:1, 1000 degrees C and 240 min. Products at the highest XRD scores were subjected to neutron permeability analyses. Menton permeability decreased With increasing thiclaie& of the,material:jncrease of molar ratio of the raw materials cohtributect to the neutron permeability of product. The lowest values of total macroscopic cross section and neutron permeability have been found for 3:2 of MgO:H3O3 ratio and 1.25 cm thickness.
Keywords: Magnesium borate; Microstructure; Neutron capture cross section; Radiation shielding; Solid state synthesis; Spectroscopy; BISMUTH; Chemistry